Spatiotemporal analyses of neural lineages after embryonic and postnatal progenitor targeting combining different reporters - Figueres-Oñate, Maria; García-Marqués, Jorge; Pedraza, Maria; De Carlos, Juan Andrés; López-Mascaraque, Laura (Frontiers in Neuroscience, 2015)
Genetic lineage tracing with electroporation is one of the most powerful techniques to target neural progenitor cells and their progeny. However, the spatiotemporal relationship between neural progenitors and their final phenotype remain poorly understood. One critical factor to analyze the cell fate of progeny is reporter integration into the genome of transfected cells. To address this issue, we performed postnatal and in utero co-electroporations of different fluorescent reporters to label, in both cerebral cortex and olfactory bulb, the progeny of SVZ neural progenitors. By comparing fluorescent reporter expression in the adult cell progeny, we show a differential expression pattern within the same cell lineage, depending on electroporation stage and cell identity. Further, while neuronal lineages arise from many progenitors in proliferative zones after few divisions, glial lineages come from fewer progenitors that accomplish many cell divisions. Together, these data provide a useful guide to select a strategy to track the cell fate of a specific cell population and to address whether a different proliferative origin might be correlated with functional heterogeneity.